Surgical treatment of hiatal hernia: A ten-year experience - Korica Milan; Sečen Svetozar; Cvijanović Radovan; Nestorov Nataša; Stanković Milan; Veljković Radovan (Vojnosanitetski Pregled)
Background/Aim. Today, hiatal hernia and the accompanying gastroesophageal reflux disease (GERD) are the most common benign disorders of the upper gastrointestinal tract. The aim of this study was to present the results of the hiatal hernia and GERD laparoscopic surgery in finding out for best type of fundoplication in each individual case. Methods. The study included 132 patients with the diagnosis of hiatal hernia and GERD, operated in the period from May 2004 to December 2014 at the Clinic for Abdominal, Endocrine and Transplantation Surgery of the Clinical Center Vojvodina, Serbia. The patients were selected for surgery on the basis of the findings of esophago-gastroscopy, barium contrast upper gastrointestinal series, 24-hour pH monitoring and esophageal manometric studies. Results. All the patients in this series underwent a posterior hiatoplasty with direct sutures. An additional mesh reinforcement was performed in 21 (16%) patients with a large hiatal hernia. There were 68 Nissen, 59 Toupet, and 5 Door fundoplications. Recently, the short-floppy Nissen fundoplication has predominantly been performed due to good postoperative outcomes. Intraoperative complications were: the parietal pleura lesion (3 patients), the spleen capsule laceration (4 patients), a minor injury of the adventitia of the distal esophagus (1 patient) and a thermal injury of the gastric fundus (1 patient). The postoperative complications were as folows: one fistula of the gastric fundus, transitory subcutaneous emphysema in the neck (5 patients), minor left-sided pleural effusions (6 patients), a transitory dysphagia (23 patients). The overall recurrence rate was 18.2% (24 patients). There was one fatal outcome. Conclusion. Laparoscopic surgery is considered a safe and effective surgical procedure for the treatment of hiatal hernia. The hiatal repair with a mesh reinforcement is recommended in selected cases. Today all consider the “short floppy” Nissen fundoplication as procedure of choice for the adequate hiatal repair.